Effect of early problem-based learning tutorial education on medical students' views about learning - ODA, Hiroshi; HASHIGUCHI, Teruto; KORIYAMA, Chihaya; HORIUCHI, Masahisa; GOTO, Masamichi; YOSHIIE, Kiyotaka; YAMAOKA, Hiroaki; UMEKITA, Yoshihisa; IMANAKA, Hiroyuki; USUKU, Koichiro (Igaku Kyoiku / Medical Education (Japan), 2008)
1) In problem-based learning (PBL) tutorials during the2nd year, general symptoms (fatigue, weight change, bleeding, fever, pain, and edema) were chosen as subjects.Changes in the students'way of thinking about how to learn were evaluated before and after PBL tutorials. 2) After tutorials students were significantly more likely to believe that their participation in tutorials was a more effective way of learning. The students'views after tutorials on listening to lectures differed between2006and2007. 3) We conclude that PBL tutorials affect medical students'views about learning.